Analysis of Health and Safety (K3), Working Environment and Employee Performance at The Container Depot - Keke, Yulianti; Krisnawati, Siti; Alfina, Intan; Sakti, Reza Fauzi Jaya; Thabah, Asep Ali (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This company focuses on operating and managing container depots that provide empty container handling services. The purpose of this study was to identify and analyze the effect of safety and health and work environment on employee performance at this container depot. The method used in this study is a quantitative method, involving 30 respondents using a saturated sampling technique and using a questionnaire measuring instrument (Likert scale) and library research. As well as data analysis using SPSS Version 27 with study methods multiple linear regression analysis, correlation coefficient, coefficient of determination, hypothesis testing using T test and F test. The results of the analysis show that there is a significant positive influence between safety and occupational health and work environment on employee performance with the existence of a multiple linear line equation with a value of Y = 1.860 + 0.367X1 + 0.599X1. The results of hypothesis testing obtained by tcount X1 8.523 and X2 10.160 > ttable 2.048. While the simultaneous test Fcount 57.638> Ftable 3.35. Based on the results of the correlation analysis, there is a positive and strong influence of 81% and 19% is influenced by other factors that are not included in this study.